Pelaksanaan Layanan Helpdesk Sistem Informasi ASN pada Instansi X - Tsulis Shoumi Fatin; Susan Febriantina; Terrylina Arvinta Monoarfa (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2023)
In the digital era, information technology has been applied to various fields, one of which is services. Currently, online-based services can make it easier for someone to ask for information or submit a complaint about something related to an institution or company. This research was conducted to determine the implementation of ASN Information System helpdesk services at institution X. This research used a qualitative method with a case study type of research. Data collection methods used are observation, interviews, and literature study. Participants in this study were employees of the SIASN helpdesk service. The results of this study indicate that the implementation of the ASN information system helpdesk service has been running quite well in terms of system usage, service appearance, and features of the service. However, in practice there are still obstacles, there is a lack of responsibility of service providers such as the response time given is not fast response. This is supported by interview statements conducted with service provider employees.